Digital Attention Economy: Concept, Phenomenon, and History in Platform Studies - Bentes, Anna (AoIR Selected Papers of Internet Research, 2026)
The attention economy has been increasingly examined in internet studies to explain sociotechnical and communicational dynamics on digital platforms. However, the commercialization of attention predates digital platforms, having shaped mass media since the 19th century. While not a new phenomenon, the attention economy assumes new contours in the digital era. This study, adopting a Foucauldian genealogical approach, investigates the ruptures between past and present logics of attention economy, analyzing their conceptual, historical, and phenomenological dimensions within critical platform studies. We identify three major ruptures in the attention economy from the mid-19th century to the present: (1) Technologies of attention management, shifting from centralized, mass-media models to distributed, algorithmic personalization; (2) The political economy of attention merchants, transitioning from advertising practices on Madison Avenue to platform-based datafication in Silicon Valley; and (3) The attentional regime, going from the modern consumer’s continuous attention crisis to a hyper-fragmented, screen-addicted user-subject. This genealogical approach highlights that historical ruptures in the attention economy are not merely technological but also involve new relationships between science, the market, and society, shaping regimes of power, knowledge, and subjectivity. By tracing these historical discontinuities, this study contributes to platform studies by offering a theoretical and historical perspective on the digital attention economy, emphasizing its specificities in the contemporary context.